A guide to cruising Northern Australia : anchorages Darwin to Carnarvon, including the Kimberleys - Richards, Leslie P. (Nightcliff, N.T. : Niblock Publishing, 2008)
"Sailboat cruising along the Northern Australian coast. Includes a list of anchorages from Darwin to Carnarvon"--Provided by publisher.
Keywords: Pilot guides -- Western Australia; Pilot guides -- Northern Territory; Sailing -- Western Australia; Sailing -- Northern Territory; Boats and boating -- Western Australia; Boats and boating -- Northern Territory